Brazil-Africa knowledge-sharing on social protection and food and nutrition security - Cristina Cirillo; Lívia Maria da Costa Nogueira; Fábio Veras Soares (International Policy Centre for Inclusive Growth (IPC-IG), 2016)
The objective of this paper is to analyse how knowledge-sharing activities between Brazil and several sub-Saharan African countries, in the fields of social protection and food and nutrition security policies and programmes, have directly and/or indirectly influenced African policies and programmes. To this end, the paper provides a summary of the recent evolution of the knowledge-sharing between Brazil and Africa in this area, as well as a summary of a recent consultation with African policymakers involved in knowledge exchange about their experience. This exercise allows us to map the African social protection and food and nutrition security programmes and instruments inspired and encouraged by the Brazilian experiences, and to understand the main challenges of this knowledge-sharing from the point of view of African policymakers. [...]
Keywords: 330; Brazil-Africa; knowledge-sharing; Social Protection; food; nutrition; security